Prevalence and comorbidities in patients diagnosed with uterus didelphys - Marcos Quispe, Myriam (2023)
The objective of this study was to identify the prevalence and comorbidities in patients diagnosed with uterus didelphys at the Hipólito Unanue National Hospital. The type of research is observational - descriptive and retrospective with an automatic approach; Taking advantage of the population to study, it was found to be made up of patients treated in the gynecology and obstetrics area of ​​the Hipólito Unanue National Hospital, during the period of the year prior to the start of this investigation (January 2018 to July 2019), the total number of registered patients there were 3127 and the sample consisted of 9 patients, the sample was non-probabilistic, in addition the selection was defined at convenience. The instrument used was the record of medical records of the patients attended. It is concluded that of the 9 patients in total, the most frequent age range was 16 to 20 years of age (44.4%), 55.6% had 1 pregnancy, 66.7% had only 1 delivery, 50% of deliveries they were premature, 33.3% had breech presentation, only 11.1% had babies with low birth weight, 62.5% had no complications during delivery, 22.22% had 1 miscarriage; In addition, it is recommended to encourage workshops that share extended information with patients in general, in order to make room for better diagnostic tests that have an impact on reproductive prognosis and associated comorbidities, to agree on an adequate treatment, timely and effective.